BRAC annual report, 2000 - BRAC (© BRAC, 2016)
1. Organisational societal vision 2. BRAC mission statement 3. List of acronyms 4. BRAC at a glance (Dec. 2000) 5. Map 6. BRAC overview 7. Rural Development Programme (RDP) 8. BRAC Urban Programme (BUP) 9. Health, Nutrition, and Population Programme (HNPP) 10. BRAC Education Programme (BEP) 11. Research and Evaluation Division (RED) 12. Support programmes 13. Governance 14. Financial statements